Ethics in IT outsourcing - Gold, Tandy (Boca Raton, FL : CRC Press, 2012)
'Preface It appears that the time has come for addressing broader ethical questions, beyond the typical focus on regulatory compliance and professional integrity. The growing public debate about financial equity within the context of a global economy is sharpening; this trend appears to be just in its infancy. It is clear that an ethical debate without a focus on the bottom line (who benefits, why and how) is at best weak--at worst, na{uFDA5}. Interested parties are welcome to join an on-going discussion at my website, www.ethicsinit.com. While these forums may raise more questions than they answer on this challenging topic, the dialogue will invariably prove dynamic and engaging. Tandy Gold, PMP December 2011'--
Includes bibliographical references and index.
Keywords: Information technology -- Contracting out -- Moral and ethical aspects; Electronic data processing departments -- Contracting out -- Moral and ethical aspects; Business ethics; Engineering ethics